2021
DOI: 10.1037/rmh0000171
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 remote learning experiences of youth with neurodevelopmental disorders in rural Appalachia.

Abstract: During the COVID-19 pandemic, a major educational shift took place-the transition from face-to-face instruction to remote learning. Although this transition impacted all learners, it is speculated that groups of vulnerable youth (i.e., those with neurodevelopmental disorders, in rural areas, from low-income families) would demonstrate significant difficulties with remote instruction. However, no work to date has investigated remote learning in these groups in rural settings. Accordingly, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…To date only one study has examined the role of routines in the outcomes of adolescents with ADHD during the COVID-19 pandemic; specifically, Becker and colleagues (2020) linked fewer routines to more remote learning difficulties. Similarly, only two studies have examined coping/ emotion regulation behaviors among youth with ADHD during the COVID-19 pandemic (Breaux et al, 2021a;McFayden et al, 2021). None of these prior studies simultaneously examined coping and routines as predictors of adjustment during the pandemic, and none examined specific coping behaviors (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date only one study has examined the role of routines in the outcomes of adolescents with ADHD during the COVID-19 pandemic; specifically, Becker and colleagues (2020) linked fewer routines to more remote learning difficulties. Similarly, only two studies have examined coping/ emotion regulation behaviors among youth with ADHD during the COVID-19 pandemic (Breaux et al, 2021a;McFayden et al, 2021). None of these prior studies simultaneously examined coping and routines as predictors of adjustment during the pandemic, and none examined specific coping behaviors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Given research on active coping strategies buffering against COVID-19 related stress (Ren et al, 2021;Tang et al, 2021), we hypothesized that adolescents who engage in more coping behaviors will experience fewer mental health symptoms, less substance use, less COVID-related stress, and less worry about the pandemic. Further, based on findings that adolescents with ADHD and poorer emotional regulation abilities display the highest symptomatology throughout the pandemic (Breaux et al, 2021a;McFayden et al, 2021), we hypothesized the association between coping behaviors and adjustment would be most pronounced for youth with ADHD. Finally, as an exploratory aim, we examined multi-group analyses examining each domain of coping behavior (i.e.…”
Section: Present Studymentioning
confidence: 99%
“…During the pandemic, children in Australia, and in many countries around the world, were required by the government to swiftly transition to learning remotely from home (henceforth ‘home learning’) unless they had an approved exemption, such as a parent working in essential healthcare. While it is likely all children have faced challenges related to this rapid and unexpected shift [ 2 ], this transition may have been particularly challenging for children with ADHD, with the in-person learning difficulties experienced by this population likely to extend to home learning [ 13 ], given challenges related to their environment and supports, transitions, and regulation. Whilst a body of emerging research is exploring the mental health impacts of the COVID-19 pandemic in children with ADHD [ 14 – 17 ], less research has focused on home learning specifically.…”
mentioning
confidence: 99%
“…The small body of existing research on home learning experiences in children with ADHD suggests that children with ADHD and their families have experienced greater home learning difficulties (HLD) compared to children without ADHD during the pandemic [ 2 , 13 ]. One study of home learning experiences in adolescents with and without ADHD ( N = 238; ages 15–17) indicated that almost a quarter of the sample were reported to have not engaged in any home learning during the survey period.…”
mentioning
confidence: 99%
See 1 more Smart Citation